Istiḥsān: Relevansi dan Implementasinya dalam Pergumulan Hukum Islam Kontemporer: Istiḥsān: Relevance and its Implementation in Contemporary Islamic Legal Struggles - Ahmad Mafaid; Purnama Hidayah Harahap; Abd Aziz Tambunan (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
The development of Islamic law continues to change in line with the evolution of time, both in social aspects and in the fields of science and technology. In practice, there are legal cases that have no basis for their establishment, or whose legal basis cannot be found with certainty, such as zakat income from lectures, which has no concrete basis in the Quran, Hadith, Ijmā’, or Qiyās. This research aims to find the legal basis for this practice thru a study of ushul fiqh. As for the method, it is a descriptive qualitative method, using a case study approach based on events occurring in society. The research findings indicate that Imam Abu Hanifah’s opinion on istiḥsān can address various contemporary issues. Although this thinking emerged due to sociological factors hundreds of years ago, it turns out that the difference in conditions did not become an obstacle and is still relevant to be applied as a legal solution in contemporary times. The implications of this research contribute to the struggles of contemporary Islamic law and serve as a reference for society in daily life in general, particularly in the practices of worship, transactions, politics, science and technology (IPTEK), as well as food, medicine, and cosmetics (POM).